Evaluation of an improved prototype mini-baghouse to control the release of respirable crystalline silica from sand movers. Issue 1 (2nd January 2018) - Alexander, Barbara M.; Esswein, Eric J.; Gressel, Michael G.; Kratzer, Jerry L.; Feng, H. Amy; Miller, Arthur L.; Cauda, Emanuele; Heil, Graeham
ABSTRACT: The OSHA final rule on respirable crystalline silica (RCS) will require hydraulic fracturing companies to implement engineering controls to limit workers' exposure to RCS. RCS is generated by pneumatic transfer of quartz-containing sand during hydraulic fracturing operations. Chronic inhalation of RCS can lead to serious disease, including silicosis and lung cancer. NIOSH research identified at least seven sources where RCS aerosols were generated at hydraulic fracturing sites. NIOSH researchers developed an engineering control to address one of the largest sources of RCS aerosol generation, RCS escaping from thief hatches on the top of sand movers. The control, the NIOSH Mini-Baghouse Retrofit Assembly (NMBRA), mounts on the thief hatches. Unlike most commercially available engineering controls, the NMBRA has no moving parts and requires no power source. This article details the results of an evaluation of generation 3 of the NMBRA at a sand mine in Arkansas from May 19–21, 2015. During the evaluation, 168 area air samples were collected at 12 locations on and around a sand mover with and without the NMBRA installed. Analytical results for respirable dust and RCS indicated the use of the NMBRA effectively reduced concentrations of both respirable dust and RCS downwind of the thief hatches. Reductions of airborne respirable dust were estimated at 99+%; reductions in airborne RCS ranged from 98–99%. Analysis of bulk samples of the dust showed the likely presence of freshly fractured quartz, a particularly hazardous form of RCS. Use of an improved filter fabric and a larger area of filter cloth led to substantial improvements in filtration and pressures during these trials, as compared to the generation 2 NMBRA. Planned future design enhancements, including a weather cover, will increase the performance and durability of the NMBRA. Future trials are planned to evaluate the long-term operability of the technology.